2012
DOI: 10.1021/jp307693y
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Oxygen Vacancies Formation and Filling Followed by in Situ Photoluminescence and in Situ EPR

Abstract: Oxygen vacancies of zinc oxide were followed by photoluminescence (PL) and electron paramagnetic resonance (EPR) spectroscopies. The green PL emission was associated with oxygen vacancies: its intensity is enhanced upon static thermal treatment under inert or under vacuum, whereas it decreases upon oxygen treatment. A unique EPR signal at g = 1.96 was measured at room temperature after thermal in situ treatment under flow of inert or oxygenated atmospheres, its double integration follows the same trends than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(129 citation statements)
references
References 74 publications
10
113
2
1
Order By: Relevance
“…3, we can observe that the EPR signal intensity increases under UV-LED illumination, and this behavior can be associated with structural and electronic order-disorder effects of both Zn or O atoms. These values are similar to those previously reported in the literature, [47][48][49][50] and a review of the subject has been reported by Hunger and Weitkamp. 56 To understand, the origins of the EPR signal could be assigned to the holes trapped on oxygen atoms, in particular, oxygen vacancies at the particle surface or bulk.…”
Section: -50supporting
confidence: 92%
See 1 more Smart Citation
“…3, we can observe that the EPR signal intensity increases under UV-LED illumination, and this behavior can be associated with structural and electronic order-disorder effects of both Zn or O atoms. These values are similar to those previously reported in the literature, [47][48][49][50] and a review of the subject has been reported by Hunger and Weitkamp. 56 To understand, the origins of the EPR signal could be assigned to the holes trapped on oxygen atoms, in particular, oxygen vacancies at the particle surface or bulk.…”
Section: -50supporting
confidence: 92%
“…[46][47][48][49][50] According to the literature, this EPR signal can be associated with possible defects that are induced in the ZnO lattice, as zinc vacancies (V Zn ), oxygen on interstitial sites (O i ), mobile electrons either in the conduction band and/or shallow donor states and oxygen vacancies ðV z O Þ. [46][47][48][49][50] However the latter is the defects most commonly accepted for this EPR signal and are assigned to singly ionized oxygen vacancy defects ðV þ1 O Þ. This is evidenced by UV-light irradiation that produces an increase in the EPR signal and is related to oxygen vacancy concentrations.…”
Section: 41mentioning
confidence: 99%
“…The derivative signals have g-values ∼ 1.9964 in both the films powder. This signal corresponds to singly ionized oxygen vacancies present in ZnO lattice [38,39] which are formed in these films during growth process when oxidation of zinc takes place by the atmospheric air during sintering process. As the g-value is less than free electron g-value of 2.0023 which indicates the donor origin of the paramagnetic centre.…”
Section: Epr Spectroscopymentioning
confidence: 99%
“…First, we note that the signal at g = 1.96, typically observed in ZnO in many morphologies [24,[38][39][40], is absent from our spectra (it was not observed for any of the samples studied). The g = 1.96 resonance has been attributed to O vacancies [24,[38][39][40], and hence associated with strong luminescence in the visible from ZnO [40,41].…”
Section: Resultsmentioning
confidence: 71%